(untitled) (Journal of Applied Learning and Teaching, 2021)
The evolution of Covid-19 in India has generated biomedical crises and various crises in teaching and learning processes. The lack of consistency in taking classes, the unsystematic methods of assessing the students, the mockery of the students as ‘Covid batch’, and the career insecurities of the students have transformed the knowledge scape of the students. During the virtual interaction sessions with the participants, the authors felt that the students’ approach towards virtual learning had been infected with insecurities, insincerities, and the fear of bleak futures. These challenges invite us to critically re-investigate and re-address the unethical evaluation practices within a broader framework of the factors that contribute to the unequal systems of knowledge production within the higher educational institutions in India. Based on these arguments, the article discusses the various factors that provoke the students to indulge in such unethical practices during Covid-19; the consequences they encounter; and the possible methods to overcome such challenges. The discussions in this article are based on a case study conducted with six postgraduate students from different higher educational institutions in West Bengal and Assam.